Heisenberg spins on an anisotropic triangular lattice: PdCrO2 under uniaxial stress. (29th December 2021) - Sun, Dan; Sokolov, Dmitry A; Waite, Richard; Khim, Seunghyun; Manuel, Pascal; Orlandi, Fabio; Khalyavin, Dmitry D; Mackenzie, Andrew P; Hicks, Clifford W
Abstract: When Heisenberg spins interact antiferromagnetically on a triangular lattice and nearest-neighbor interactions dominate, the ground state is 120° antiferromagnetism. In this work, we probe the response of this state to lifting the triangular symmetry, through investigation of the triangular antiferromagnet PdCrO2 under uniaxial stress by neutron diffraction and resistivity measurements. The periodicity of the magnetic order is found to change rapidly with applied stress; the rate of change indicates that the magnetic anisotropy is roughly forty times the stress-induced bond length anisotropy. At low stress, the incommensuration period becomes extremely long, on the order of 1000 lattice spacings; no locking of the magnetism to commensurate periodicity is detected. Separately, the magnetic structure is found to undergo a first-order transition at a compressive stress of ∼0.4 GPa, at which the interlayer ordering switches from a double-to a single- q structure.